How can destination management organisations enhance their social media marketing communication in the field of sports tourism? - Silke Bambauer-Sachse; Carmen Sarah Einsle (Tourism and Hospitality Management)
Purpose – Sports tourism is one of the fastest-growing tourism sectors. Based on the uses and gratifications theory, this study investigates how different characteristics (i.e., information, entertainment, and engagement value) of destination management organisations’ (DMO) social media posts on sports tourism influence potential sports tourists’ social media usage, booking intentions, and intentions to spread positive word of mouth (WOM) about the destination. Methodology – We collected the study data through a combination of an online survey and paper-and-pencil questionnaires and used PLS-SEM to analyse the hypothesised relationships. Findings – Our results demonstrate that a high information value of a DMO’s post triggers booking intentions, while posts additionally need to have a high engagement value when it is also important to increase social media users’ WOM, and a third post characteristic – entertainment value – is essential when future social media usage intentions are to be increased. Originality of the research – The results of our study enable DMOs to choose the most critical post characteristics (information, entertainment, and engagement value) according to the respective objective pursued with their social media communication (i.e., increasing booking intentions, WOM, or future social media usage intentions). Prior research has not provided such insights that can enhance communication strategies.